Case Report: A Review of the Literature on Spinal Intradural Hemangiopericytoma With Spinal Cord Infiltration and a Case Report - Chunyang, Liu; Huiqin, Zhu; Mo, Sun; Yubo, Wang; Xianfeng, Zhang (Frontiers in Surgery, 2020)
Purpose: Primary spinal intradural hemangiopericytoma (HPC) with spinal cord infiltration is rare. The purposes of this study were to investigate the clinical features of intradural HPC with spinal cord infiltration and to explore the related factors affecting tumor recurrence. Methods: We report a case of intramedullary HPC with intramedullary infiltration of the thoracic spine. The relevant literature was searched for with PubMed, and clinical data were extracted from the included studies. Clinical patient data were described and statistically analyzed. Then, Kaplan-Meier (KM) curves were used to describe the relapse-free survival (RFS) of patients in different groups, and the log-rank test was used for evaluation. Results: A total of 11 cases of spinal intradural HPC with spinal cord infiltration were included (including the case described in this report). Further data analysis showed that sex (P = 0.249), age (P = 0.876), tumor location (P = 0.524), and postoperative radiotherapy (P = 0.12) had no significant influence on RFS. The range of tumor resection (P = 0.004) and the WHO grade (P = 0.014) significantly affect the patient RFS. Conclusion: RFS was higher in patients with total tumor resection than in patients with subtotal tumor resection. The patients with lower WHO grade have better RFS. Total tumor resection is the primary objective of surgical treatment of spinal intradural HPC with spinal infiltration. Long-term postoperative follow-up is considered necessary.